Medical Record File Retention Process At Banyumulek Public Health Center To Improve The Quality Of Medical Record Services - Sutomo, Suswinda Yuli; Usman, Arip; Fahri, Ahmad (Fakultas Ilmu Kesehatan, 2025)
Medical record retention is a crucial aspect of medical record management that directly impacts the quality of healthcare services. As a primary healthcare facility, Banyumulek Community Health Center (Puskesmas), facing challenges in managing active and inactive medical records due to limited storage space and increasing patient visits, faces challenges in managing active and inactive medical records due to limited storage space and the increasing number of patient visits. This study aims to analyze the medical record retention process at Banyumulek Community Health Center and efforts to improve the quality of medical record services. A descriptive approach was used, collecting data through observation, interviews, and documentation studies of medical record staff. The results indicate that the implementation of medical record retention does not fully comply with standard operating procedures, particularly regarding the scheduling of retention and destruction of inactive files. This situation impacts service efficiency, speed of file retrieval, and the tidiness of the storage system. Therefore, consistent implementation of retention policies, the development of clear standard operating procedures (SOPs), and increased competency of medical record staff are needed to support the improvement of the quality of medical record services at Banyumulek Community Health Center.